Assessment of false transmitters as treatments for nerve agent poisoning. (15th March 2020) - Whitmore, Charlotte; Lindsay, Christopher D.; Bird, Mike; Gore, Samuel J.; Rice, Helen; Williams, Rebecca L.; Timperley, Christopher M.; Green, A. Christopher
Highlights: AMECh and ADECh act as false transmitters at human acetylcholine receptors. Administration of MECh and DECh led to recovery in a soman-exposed functional neuromuscular preparation. Consistent with activity as false transmitters, the functional recovery was maintained after washout. Abstract: Nerve agents inhibit acetylcholinesterase (AChE), leading to a build-up of acetylcholine (ACh) and overstimulation at cholinergic synapses. Current post-exposure nerve agent treatment includes atropine to treat overstimulation at muscarinic synapses, a benzodiazepine anti-convulsant, and an oxime to restore the function of AChE. Aside from the oxime, the components do not act directly to reduce the overstimulation at nicotinic synapses. The false transmitters acetylmonoethylcholine (AMECh) and acetyldiethylcholine (ADECh) are analogs of ACh, synthesised similarly at synapses. AMECh and ADECh are partial agonists, with reduced activity compared to ACh, so it was hypothesised the false transmitters could reduce overstimulation. Synthetic routes to AMECh and ADECh, and their precursors, monoethylcholine (MECh) and diethylcholine (DECh), were devised, allowing them to be produced easily on a laboratory-scale. The mechanism of action of the false transmitters was investigated in vitro . AMECh acted as a partial agonist at human muscarinic (M1 and M3 ) and muscle-type nicotinic receptors, and ADECh was a partial agonist only at certain muscarinic subtypes. Their precursors acted as antagonists at muscle-type nicotinic, but not muscarinic receptors. Administration of MECh and DECh improved neuromuscular function in the soman-exposed guinea-pig hemi-diaphragm preparation. False transmitters may therefore help reduce nerve agent induced overstimulation at cholinergic synapses.